Purification and properties of dihydroxyacetone kinase from Klebsiella pneumoniae. - Johnson, E A (1984)
Dihydroxyacetone (DHA) kinase of Klebsiella pneumoniae, a gene product of the dha regulon responsible for fermentative dissimilation of glycerol and DHA, was purified 120-fold to a final specific activity of 10 mumol X min-1 X mg of protein-1 at 30 degrees C. The enzyme, a dimer of a 53,000 +/- 5,000-dalton polypeptide, is highly specific for DHA (Km, ca.4 microM). Glycerol is not a substrate at 1 mM and is not an inhibitor even at 100 mM. The enzyme is not inhibited by 5 mM fructose-1,6-diphosphate. Ca2+ gives a higher enzyme activity than Mg2+ as a cationic cofactor. Escherichia coli glycerol kinase acts on both glycerol and DHA and is allosterically inhibited by fructose-1,6-diphosphate. Antibodies raised against E. coli glycerol kinase cross-reacted with K. pneumoniae glycerol kinase but not with K. pneumoniae DHA kinase.